Bromodomain biology and drug discovery - Zaware, Nilesh (Nat Struct Mol Biol, 2019)
The bromodomain (BrD) is a conserved structural module found in chromatin- and transcription-associated proteins that acts as the primary reader for acetylated lysine residues. This basic activity endows BrD proteins with versatile functions in the regulation of protein-protein interactions mediating chromatin-templated gene transcription, DNA recombination, replication and repair. Consequently, BrD proteins are involved in the pathogenesis of numerous human diseases. In this Review, we highlight our current understanding of BrD biology, and discuss the latest development of small-molecule inhibitors targeting BrDs as emerging epigenetic therapies for cancer and inflammatory disorders.